Garden plants and butter knives : the effects of lexical and relation priming on nominal compound processing by native and non-native speakers of English - Malenica, Frane (Array, 2019)
Compounds are a frequent occurrence in the English language, but the way in which speakers, both native and non-native, process compounds is still a topic of discussion. Two factors have an influence on the recog-nition speed of compounds – lexical priming and relation priming. The former refers to faster recognition if a target and a prime compound share a common lexeme, while the latter refers to the inner relationships be-tween modifiers and heads within a compound. The study conducted by Gagné & Spalding (2004) shows a significant effect of relation priming on recognition of familiar compounds, while De Cat et al. (2015) report that highly proficient non-native participants use similar strategies for processing compounds as native speakers. The aim of this paper is to rep-licate these results by using sense-nonsense tasks with familiar com-pounds and native and highly proficient non-native participants to exam-ine the effects of lexical and relation priming in these two groups. We hypothesize that the native speakers should provide faster reaction times and higher accuracy rates but that both groups would display similar fa-cilitation effects with different types of primes, which the results of the study confirm.